PARÂMETROS ANTROPOMÉTRICOS DE CAMUNDONGOS (B6129SF2/J) DO BIOTÉRIO DA UNIJUÍ - Bruinsma, Ariane L.; Pietczak, Natália; Basso, Eloisa G. D. P.; Baldissera, Fernanda G.; Heck, Thiago G.; Ludwig, Mirna S. (Salão do Conhecimento, 2013)
Resumo